Made to tremble : how anxiety became the best thing that ever happened to my faith - Linne, Blair (B&H Publishing, 2025)
"Through gripping narrative and compelling biblical teaching, Blair Linne shares her own transformative journey through crippling anxiety and panic attacks. She helps the reader escape out of shame, isolation, quick fixes, and spiritual platitudes with profound lessons on what it means to be human and how it feels to not only know the God of Peace, but the peace of God."--